Special needs trusts : protect your child's financial future - Urbatsch, Kevin; Jones, Jessica Farinas (Nolo, 2025)
Presents advice on setting up and managing a special needs trust, covering trust benefits, funding, duties of trustees, pooled trusts, taxes, wills, and death of beneficiaries.